DAN FAKTOR RISIKO PREVALENSI KOKSIDIOSIS PADA PEDET DI KABUPATEN MAGELANG - , HANANTA SETYA NUGRAHA, Prof. Dr. drh. Bambang Sumiarto, SU.,M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coccidiosis is a disease which caused the protozoa Eimeria sp. Coccidia in cattle generally occurs as a subclinical disease resulting in weight loss weight due to digestive disorders, lower body resistance, and sometimes lead to death. The researchâs purpose was to determine the prevalence and risk factors of coccidiosis in calves at Magelang regency, Central Java. The samples obtained by multiple stage, simple random and cluster sample. A total of 133 samples from 89 farmers were taken as the study sample. Samples were taken from calves aged less than one year on a per-rectal or shortly after defecation. Obtained samples were examined using centrifugal flotation method. Field data obtained from the questionnaires were filled based on interviews with farmers and direct observation of stall conditions and livestock. The data were analyzed using Chi-square to determine the association and odds ratio (OR) to measure the strength of the association. The result of study showed that the prevalence of coccidiosis at amount of 45.9%. Calf type factor (P=0,002